Andrew Mayos Human Capital Approach Model in the Management of More Productive Human Resources in Private Islamic Higher Education - Rusdiana, A.; Mui’n, Abdul (International Journal of Publication and Social Studies, 2020)
This research is intended to identify Andrew Mayo’s More Productive Human Resource Approach Model in private Islamic higher institutions in the area of the Coordinator of Private Islamic Region Region II Colleges of West Java and Banten. This research uses a qualitative method with descriptive research type. Based on Andrew Mayo’s human capital approach, to develop a sustainable and competitive organizational climate, five main components of Mayo must be implemented, namely; individuals who have the ability, motivation, organizational climate, work group effectiveness, and leadership. Realizing the importance of the role of human resources in the activities of Islamic religious higher education institutions must be able to manage human resources as well as possible, because the key to the success of an organization or institution is not only in terms of technological superiority and availability of funds, but also needs to pay attention to human factors. Based on observations, the results of this study indicate that: there are still many private Islamic tertiary educational institutions in the Kopertais Region II area of West Java and Banten that have not implemented an optimal human resource approach, as suggested by Mayo, especially in aspects of individual capabilities and individual motivation.